The analysis of competitive positions of building services in the Republic of Belarus - Taiskan, Yue (Journal of the Belarusian State University. Economics, 2018)
The article reviews the current state of building services in the internal and external market. The prospects and problems of development of the construction sector of the Republic of Belarus are analysed.